Optical Flow-Hermite and Fuzzy Q-Learning Based Robotic Navigation Approach - Moya-Albor, Ernesto; Brieva, Jorge; Ponce, Hiram; Gomez-Coronel, Sandra L. (My University, 2021)
The present paper presents a bio-inspired optical flow approach to autonomous robotics navigation. It uses a Fuzzy Q-Learning (FQL) method to take decisions in an unknown environment through a reinforcement signal. The proposed method was implemented in a virtual robotics system using the V-REP software and in communication con MATLAB. The preliminary results show that the robot was able to navigate successfully in unknown environments. © 2021 IEEE.
Keywords: Air navigation; Biomimetics; MATLAB; Reinforcement; Reinforcement learning; Robots; Visual servoing; Autonomous robotics; Fuzzy-Q-learning